Analysis of magnetic field magnitude under the extra-high-voltage airway (SUTET) with route of Cilegon - Cibinong - Retno Hadi Winoto; Jayanudin Jayanudin; Nuryoto Nuryoto (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
Today, electricity is a very important need so the demand for electricity increases in the world. To meet the electricity needs of the community, the Indonesian government through the state electricity company (PT. PLN) has built electric power networks starting from power plants to transmission lines that can supply electricity to consumers. To reduce power losses along the transmission lines, extra-high-voltage (EHV) is needed. However, the use of this EHV also produces electric and magnetic fields around the conducting wires. This causes anxiety for people, especially people who live in the areas of EHV Airways. The large magnetic field around the conductor wires is feared to have a detrimental impact on people who live near transmission lines. The threshold for the value of the magnetic field that is permitted according to the regulations of MENKES/SK/XI/2002 and SPLN 112:1994 is 500 μT. For this reason, this research was conducted to determine the magnitude of the magnetic field around the conductor wires of the EHV Airway and to determine the effect of the magnetic field on the environment. The methods used in this research were direct measurements and theoretical calculations. The results of the research prove that the value of the magnetic field that appears, both in terms of calculations and in terms of measurements, is still below the allowable threshold both by WHO and IRPA as well as by MENKES/SK/XI/2002 and SPLN 112:1994